Gender and socio-economic differencesin South African consumers’ sentimentstoward marketing practices - Thérèse Roux (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Studies on modern consumers’ sentiments toward marketing in an emerging market context are vital. This paper compares demographic diff erences in South African consumers’ sentiment toward marketing. Data were collected via a survey with 444 diverse consumers residing in the Tshwane metropolitan area. The fi ndings revealed that South African males are signifi cantly less satisfi ed with marketing communication practices compared to females. Consumers earning lower income were signifi cantly less positive towards marketing in general as well as product quality, price, and selling practices. Afrikaans-speaking consumers’ attitudes were less positive towards marketing communication. The fi nding can guide the marketing industry to advance its image by adjusting its practices and coordinating with the government and other stakeholders to collaborate.